Untargeted metabolomics of Aloe volatiles: Implications in pathway enrichments for improved bioactivities - Nehal Batra; Priyankar Dey (Heliyon)
Enhancing the production of economically and medically important plant metabolites by genetic and metabolic manipulation is a lucrative approach for enhancing crop quality. Nevertheless, the task of identifying suitable biosynthetic pathways related to certain bioactivities has proven to be challenging due to the intricate interconnections of the major metabolic and biochemical processes in commercially important plants. The commercial significance of plants belonging to the genus Aloe stems from their extensive utilization across several industries, such as cosmetics, pharmaceuticals, and wellness items, due to their medicinal properties. In the present study, we have utilized a reverse association approach to identify potential target metabolic pathways for enhancing the production of commercially important metabolites of Aloe spp., based on their metabolic pathway enrichment profile. The leaves of five highly utilized Aloe sp. were subjected to untargeted gas chromatography-mass spectrometry analysis followed by testing of free-radical scavenging effects against components of the Fenton and Haber-Weiss reaction. Through the application of appropriate bioinformatics tools, we identified distinct phytochemical classes and determined the enrichment of their corresponding biosynthetic pathways, associated the pathways with bioactivities, and also identified the inter-relation between the commonly enriched pathways. The strong association between metabolic pathways and antioxidant potentials suggested the necessity to enhance distinct but closely related metabolic pathways in order to enhance the quality of Aloe spp. and maximize their antioxidant effects for commercial exploitation in cosmetic industries.